The estimation of risk management efficiency and its determinants - Uzma Noreen, (Penerbit Universiti Kebangsaan Malaysia, 2020)
This research aims at finding risk management efficiency and its determinants of non-life insurers operating in Pakistan. This study applies Data Envelopment Analysis (DEA) to determine the efficiency scores for risk management practices of firms over the period 2009-2018. Tobit model is applied to identify factors influencing risk management efficiency of firms. DEA results obtained indicate that the overall average efficiency score increases from 68% in 2009 to 76% in 2018. Tobit estimates show that the age and firm size has a significantly positive relationship with risk management efficiency of firms. The study suggests that firms at lower efficiency frontier could improve their efficiency level by performing better in terms of underwriting and investment activities as well as enhancing the value-added of the firms. The study also recommends that non-life insurers should adopt a multifaceted approach in managing the risks to derive greater benefits from their businesses.